PERADABAN ISLAM PERIODE DAULAH ABBASIYAH DALAM MENINGKATKAN MINAT MEMBACA MASYARAKAT - Budiyati Budiyati; Anisa Dwi Makrufi (VICRATINA, 2018)
Indonesia is a large nation with abundant natural resources. Unfortunately, this is not balanced with human resources (especially) in terms of reading literacy which is still low. Though the population of Indonesia is a Muslim majority and the first revelation that comes down is related to the command to read. If we look at the history of Islamic civilization, people in the Abbasid Daula era can be said to have a high literacy reading rate. This is evidenced by the establishment of the largest library in history, Baitul Hikmah. This article aims to find out how to increase interest in reading Indonesian society such as in the Abbasid era. The method used in this study is a literature study with a descriptive analysis approach. The strategy developed by the Abbasid era caliph in terms of increasing literacy reading included establishing many libraries to remote areas, translating books, and providing great rewards for book writers. The current context, in an all-digital era, should Indonesian people be more advanced in terms of literacy reading.